2016
DOI: 10.1007/s10858-015-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

UTOPIA NMR: activating unexploited magnetization using interleaved low-gamma detection

Abstract: A growing number of nuclear magnetic resonance (NMR) spectroscopic studies are impaired by the limited information content provided by the standard set of experiments conventionally recorded. This is particularly true for studies of challenging biological systems including large, unstructured, membrane-embedded and/or paramagnetic proteins. Here we introduce the concept of unified time-optimized interleaved acquisition NMR (UTOPIA-NMR) for the unified acquisition of standard high-γ (e.g. 1H) and low-γ (e.g. 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Alternatively, NMRoptimized, smaller MSP constructs (see Section 'Choosing the MSP construct') can be used to sufficiently increase molecular tumbling and allow the usage of regular 13 C-13 C transfer sequences . It has also been successfully shown that TOCSY-based 13 C-13 C transfer, combined with 13 C detection, can be used to study the transmembrane region of OmpX in MSDP1D1 NDs (Viegas et al, 2016). Remarkably, when using unified time-optimized interleaved acquisition (UTOPIA) setups this information can be obtained for free during the acquisition of a 3D NOESY-TROSY experiment (Viegas et al, 2016).…”
Section: Nmr Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, NMRoptimized, smaller MSP constructs (see Section 'Choosing the MSP construct') can be used to sufficiently increase molecular tumbling and allow the usage of regular 13 C-13 C transfer sequences . It has also been successfully shown that TOCSY-based 13 C-13 C transfer, combined with 13 C detection, can be used to study the transmembrane region of OmpX in MSDP1D1 NDs (Viegas et al, 2016). Remarkably, when using unified time-optimized interleaved acquisition (UTOPIA) setups this information can be obtained for free during the acquisition of a 3D NOESY-TROSY experiment (Viegas et al, 2016).…”
Section: Nmr Applicationsmentioning
confidence: 99%
“…One of the greatest potentials of using NMR spectroscopy to study MPs incorporated into nanodiscs is the possibility of determining their 3D structure in solution, in a closeto-native and active conformation. Although the molecular weight of the MP-ND complex is high, it should still be under 200 kDa and thus suitable for being studied by modern NMR techniques (Shenkarev et al, 2010a;Klammt et al, 2012;Opella 2013;Viegas et al, 2016). The first MP structure determined by NMR and using the ND technology was of the 180-residues bacterial outer-membrane protein OmpX (PDB code: 2M06) .…”
Section: Structure Determinationmentioning
confidence: 99%
“…Examples of the three types of experiments involving two receivers: (a) interleaved experiments, e.g. interleaved COSY (A‐A COSY and X‐X COSY); (b) parallel acquisition experiments, e.g.…”
Section: Three Types Of Experiments For Two Receiversmentioning
confidence: 99%
“…[4.5] In this manuscript we focus on experiments involving simultaneous detection of two abundant and highly sensitive nuclei, 1 H and 19 F. Many of the experiments discussed in the succeeding texts can be (and in many Figure 1. Examples of the three types of experiments involving two receivers: (a) interleaved experiments, [28] e.g. interleaved COSY (A-A COSY and X-X COSY); (b) parallel acquisition experiments, [2] e.g.…”
Section: Three Types Of Experiments For Two Receiversmentioning
confidence: 99%
See 1 more Smart Citation